Screening of delayed-onset hearing loss in preschool children in the mid-south of China. (August 2013) - Chen, Guanming; Fu, Siqing; Luo, Shaojun; Zhang, Wei; Yang, Guoqiang
Abstract Objective: Newborn hearing screening has been successfully implemented worldwide to improve the detection of hearing loss. However, delayed-onset hearing loss subsequent to newborn hearing screening remains a concern. This study aimed to investigate the prevalence of delayed-onset hearing loss in preschool children who previously passed newborn hearing screening in Hubei Province in mid-south China. Design: Preschool children were screened by transient evoked otoacoustic emission (TEOAE) for delayed-onset hearing loss. Children referred after the TEOAE screening were assessed audiologically. Study sample: Between March 2010 and September 2011, 28 546 preschool children (4.86 ± 1.67 years old), who had passed newborn hearing screening were targeted for screening from four cities in Hubei Province, China. Results: During the study period, 540 children (1.89%) were referred for audiologic assessment and 22 (0.77/1000) of them had permanent delayed-onset hearing loss, including 8 (0.28/1000) with bilateral moderate hearing loss, 10 (0.35/1000) with mild bilateral hearing loss, 2 (0.07/1000) with unilateral moderate hearing loss, and 2 (0.07/1000) with unilateral mild hearing loss. Conclusions: Despite the success of newborn hearing screening, the provision of hearing screening in preschool remains essential for identifying delayed-onset hearing loss.